2017
DOI: 10.1111/cid.12516
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial for the biological evaluation of two nanostructured biphasic calcium phosphate biomaterials as a bone substitute

Abstract: B1 group showed the greatest amount of newly formed bone after 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…Thus, further experimentation is necessary to elucidate this question. Importantly, a recent clinical trial 37 reported histologic results in human extraction sockets grafted with SBC-B comparable to the present data, suggesting similarities in biologic behavior of the biomaterial in extraction socket defects of diferent species.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, further experimentation is necessary to elucidate this question. Importantly, a recent clinical trial 37 reported histologic results in human extraction sockets grafted with SBC-B comparable to the present data, suggesting similarities in biologic behavior of the biomaterial in extraction socket defects of diferent species.…”
Section: Discussionsupporting
confidence: 87%
“…34 According to manufacturer guidelines, and several other studies using ceramic biomaterials as a bone substitute, their hydration should be done with the patient's blood. [35][36][37][38] However, the availability of blood material in the region to be addressed may not be sufficient to meet the need, especially when large quantities of material is required. In this case, peripheral sources of blood collection may be necessary for the correct hydration of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations have indicated the necessity for the use of other types of bone substitutes that allow an adequate process of bone tissue formation with reduction of morbidity to the host 8,9 . Among the bone substitute alternatives to autogenous bone graft, osteoconductive biomaterials, such as deproteinized bovine bone (DBB) and biphasic ceramics, which are composed of hydroxyapatite and beta-phosphate tricalcium (HA/TCP), have highly diffused clinical application [8][9][10] . However, the low rate of reabsorption of hydroxyapatite present in both biomaterials implies its complete replacement by bone tissue, and the remnants of these bone substitutes have been observed in the recipient site until the implant placement 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the bone substitute alternatives to autogenous bone graft, osteoconductive biomaterials, such as deproteinized bovine bone (DBB) and biphasic ceramics, which are composed of hydroxyapatite and beta-phosphate tricalcium (HA/TCP), have highly diffused clinical application [8][9][10] . However, the low rate of reabsorption of hydroxyapatite present in both biomaterials implies its complete replacement by bone tissue, and the remnants of these bone substitutes have been observed in the recipient site until the implant placement 9,10 . In addition, these remaining particles do not participate in the direct osseointegration process of the implants due to the lack of vitality of this tissue 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These stages guide the osteoblasts to gradually differentiate into osteocytes and facilitate osteogenesis (4); therefore, high bioactivity and biocompatibility, osteoconduction and biodegradability are necessary characteristics in an alternative material that may facilitate bone regeneration (5). In the past three decades, various bone substitutes with high biocompatibility and good osteoconduction have been reported and have been applied to repair bone defects (6)(7)(8)(9); however, insufficient bioactivity of these materials has restricted the repair process (8). Therefore, high biocompatibility, biodegradability and osteogenic potential are considered desirable for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%